2011
DOI: 10.1103/physreve.83.046107
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of signal response at an arbitrary node of a complex network

Abstract: Signal detection is generally related to network structure in both biological and engineering systems, and enormous effort has been putting into understanding the mechanism of amplification of weak signals in the aspects of self-tuning and scale-free topology. Here, we show that a third way of signal amplification exists, which does not require the scale-free topology as a necessary condition. This approach can effectively amplify the signal at an arbitrary node in a complex network by adaptively adjusting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 13 publications
0
13
0
1
Order By: Relevance
“…Ideally, an approach that amplifies signals using only local information would be interesting to have. We are currently pursuing this direction [35].…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, an approach that amplifies signals using only local information would be interesting to have. We are currently pursuing this direction [35].…”
Section: Discussionmentioning
confidence: 99%
“…Of special relevance is the propagation and enhancement of resonant collective behaviour across a network due to the application of weak external signals because of its importance in both biological and man-made information-processing systems. In this regard, it has been recently studied the amplification of the response to weak external signals in networks of bistable signaling devices [14][15][16][17]. In these works, however, the robustness of the signal amplification against disordered distributions of external signals was not considered.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that random fluctuations can enhance the response to weak periodic driving, as observed in many different physical, chemical and biological scenarios [8][9][10]. Recently, amplified signal response in complex network of coupled oscillators has drawn considerable attention [7,[11][12][13][14][15][16]. It has been found that the weak external signals can be amplified by the heterogeneity in degree of the network [7,11,12], adaptive coupling weights between (a) hzhlj@ustc.edu.cn the signal node and its neighbors [13], neuronal diversity on complex networks [14] and a multilayer feedforward network [15].…”
mentioning
confidence: 99%
“…Recently, amplified signal response in complex network of coupled oscillators has drawn considerable attention [7,[11][12][13][14][15][16]. It has been found that the weak external signals can be amplified by the heterogeneity in degree of the network [7,11,12], adaptive coupling weights between (a) hzhlj@ustc.edu.cn the signal node and its neighbors [13], neuronal diversity on complex networks [14] and a multilayer feedforward network [15]. A one-body theory which gave analytic expressions of the gain and the degree of the unit with the maximum response to the input signal in terms of the coupling strength was also developed [16].…”
mentioning
confidence: 99%
See 1 more Smart Citation